2005
DOI: 10.1128/iai.73.8.4922-4933.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans α Strains Preferentially Disseminate to the Central Nervous System during Coinfection

Abstract: Cryptococcus neoformans is a fungal pathogen that has evolved over the past 40 million years into three distinct varieties or sibling species (gattii, grubii, and neoformans). Each variety manifests differences in epidemiology and disease, and var. grubii strains are responsible for the vast majority of human disease. In previous studies, ␣ strains were more virulent than congenic a strains in var. neoformans, whereas var. grubii congenic a and ␣ strains exhibited equivalent levels of virulence. Here the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 81 publications
(75 reference statements)
3
117
0
12
Order By: Relevance
“…grubii strain KN99a was equivalent to KN99a in virulence. However, KN99a cells more readily penetrate the blood-brain barrier than KN99a cells during co-infection (Nielsen et al 2005). Thus, differences in virulence potential between a and a strains in var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…grubii strain KN99a was equivalent to KN99a in virulence. However, KN99a cells more readily penetrate the blood-brain barrier than KN99a cells during co-infection (Nielsen et al 2005). Thus, differences in virulence potential between a and a strains in var.…”
Section: Discussionmentioning
confidence: 99%
“…However, following co-infection with the var. grubii congenic strains, the a strain more efficiently colonized the central nervous system than the a mating-type strain and provided evidence for a contribution of the MAT locus at least during co-infection (Nielsen et al 2005).…”
mentioning
confidence: 95%
“…It has been reported that MATα is more virulent than the opposite type MATa 29 . Moreover, in coinfection with both mating types, the MATα strains more likely disseminate to the central nervous system which might explain the prevalence among the clinical isolates 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Strains were made in C. neoformans KN99α (Nielsen et al 2005) with standard growth at 30°C in yeast peptone dextrose (YPD) medium. For capsule induction, an overnight culture in YPD was washed, resuspended in DMEM, and grown at 37°C in 5% CO 2 .…”
Section: Materials Strains and Cell Growthmentioning
confidence: 99%